Factors that Trigger the Organizational Citizenship Behavior of Millennial Generation Employees - Muttaqiyathun, Ani; Nurmaya, Ema; Lukmananti, Agrestina; Fitriani, Melisa (Journal of Social Research, 2023)
The millennial generation is often referred to as Generation Y. Researchers are still debating the year they were born, but most estimate that this generation was born in the last 22-40 years. This generation has now reached maturity, their talents have colored the world of work, especially in the business sector. Generation Y grew up with technological developments, making it easier to find information, faster to learn, aggressive, creative, and innovative than the previous generation. They are seen as having unique characteristics, expectations, priorities, and work ethic so they are not afraid of change. This unique character is very important for organizations to manifest Organizational Citizenship Behavior. This is important to support organizational performance, namely increasing the organizational ability to adapt to environmental changes such as and improve quality in a sustainable manner. The purpose of this study is to analyze the factors that can trigger the emergence of Organizational Citizenship Behavior. The research object is focused on employees who are included in the millennial generation. The sample is determined purposively from the population with certain criteria. Data collection was carried out using a questionnaire via Google Forms. Data analysis used multiple regression analysis techniques. The research findings conclude that the Adversity Quotient has no effect on Organizational Citizenship Behavior, but Transformational Leadership, Organizational Commitment, and Job Satisfaction are stated to have a significant positive effect on Organizational Citizenship Behavior.